2019
DOI: 10.1016/j.jstrokecerebrovasdis.2019.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of miR-125b-5p and miR-206 in Acute Ischemic Stroke Patients After Recanalization Treatment: A Prospective Observational Study

Abstract: Introduction: Multiple microRNAs (miRNAs) participate in the response to hypoxic/ ischemic and ischemia-reperfusion events. However, the expression of these miRNAs in circulation from patients with acute ischemic stroke (AIS) receiving recanalization treatment has not been examined, and whether they are associated with the severity and outcome of stroke is still unknown. Materials and methods: In this prospective cohort study, plasma levels of miR-125b-5p, miR-15a-3p, miR-15a-5p, and miR-206 were measured at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 37 publications
1
20
0
2
Order By: Relevance
“…MiR-206, a muscle-enriched miRNA (myomiR), has an important role in myogenic differentiation [ 28 ]. MiR-206 was reported to be positively correlated with stroke severity [ 29 , 30 ] in humans and infarct volume in an animal model of embolic stroke [ 31 ], serving as a detrimental biomarker. Overexpression of miR-206 inhibits neuronal cell viability and proliferation, interfering with neurodevelopment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-206, a muscle-enriched miRNA (myomiR), has an important role in myogenic differentiation [ 28 ]. MiR-206 was reported to be positively correlated with stroke severity [ 29 , 30 ] in humans and infarct volume in an animal model of embolic stroke [ 31 ], serving as a detrimental biomarker. Overexpression of miR-206 inhibits neuronal cell viability and proliferation, interfering with neurodevelopment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo experiment demonstrated that miR-125a-5p regulates blood brain barrier function [14]. MiR-125b-5p has previously been shown to be a predictive biomarker candidate for ischemic stroke outcomes [15,16]. MiR-433 is highly expressed in the brain tissue [11].…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow derived mesenchymal stem cells EVs have been reported to home in the infarct area after transplantation and have therapeutic effects such as endogenous neurogenesis, increase the number of axons, and improve vital functions of animals [ 63 , 64 ]. When incorporated with different miRNAs, MSC-derived EVs were able to promote a neuroprotective response [ [65] , [66] , [67] ]. In some studies, MSCs overexpressing specific miRNAs were chosen and were able to be passed on to the daughter EVs.…”
Section: Future Treatments: Limiting Reperfusion Damage and Recovering From Ischemic Strokementioning
confidence: 99%